Development of physical culture and sport on Volyn in 1930–1950 years - Войнаровський, А. М. (Slobozhanskyi Herald of Science and Sport, 2011)
The article deals with historical questions of origin of physical culture and sports in western lands (Poland 30s of the twentieth century and USSR 40-50 s of the twentieth century). The system of lead through of sporting measures is reflected in this region.